Endometriosis and strategies of fertility preservation: a systematic review of the literature. (November 2020) - Calagna, Gloria; Della Corte, Luigi; Giampaolino, Pierluigi; Maranto, Marianna; Perino, Antonino
Abstract: Endometriosis is a common chronic inflammatory disorder, often causing both pain and infertility. It is estimated that 25–50 % of patients undergoing fertility treatments have had endometriosis as it involves an impairment of the ovarian reserve. For these reasons, endometriosis has been highlighted as a condition that may require a fertility preservation procedure, while being benign in nature. The aim of this review is to summarize the current evidence on fertility preservation techniques for patients affected by endometriosis, focusing on the main characteristics of the different approaches. A systematic review of literature was performed by searching in the main electronic databases (MEDLINE, EMBASE, Web of Science, Scopus, ClinicalTrial.gov, OVID and Cochrane Library), from their inception to February 2020 for studies testing fertility preservation (FP) techniques. Only scientific publications in English were included. Risk of Bias Assessment was performed. Eight articles were included in the study: 3 case reports (one paper reporting 2 cases), 1 prospective longitudinal analysis with only 1 reported case with criteria for inclusion in the review, 2 retrospective observational studies and 2 retrospective cohort studies. The results of our analysis showed embryo (1 article), oocyte (4 articles) and ovarian tissue cryopreservation (3 articles) as preservation methods proposed in international literature for patients with endometriosis. Only few authors reported details on successive outcomes. After ovarian tissue transplantation, 1 pregnancy with IVF and 1 case of endocrine function/ovulation recovery were described; six of 16 endometriotic patients, who underwent embryo cryopreservation, experienced livebirths after successive embryo-transfer; in a large series of 485 patients performing oocyte cryopreservation, an overall cumulative live-birth rate/patient of 46.4 % (225 babies) was reported. Based on the risk of premature ovarian failure related to endometriosis, the offer of FP techniques to these patients has significantly increased, as well as the reported experiences in recent medical literature. However, further studies concerning risks, benefits, effectiveness and cost-effectiveness are needed.